Multifaceted applications of microalgal biomass valorization to enriched biorenewables, a review of futuristic biorefinery paradigm. (February 2022) - Rehmanji, Mohammed; Singh, Rabinder; Nesamma, Asha Arumugam; Khan, Nida Jamil; Fatma, Tasneem; Narula, Alka; Jutur, Pannaga Pavan
Abstract: Microalgal biorefineries pave a significant impact in addressing current global challenges in the energy, environment and health care sectors. In such context, our current review focuses on the providing an ideal solution of a futuristic biorefinery-based model which favours production of biofuels and biorenewables employing various biomass improvement strategies. For instance, the combinatorial impacts of using wastewater and carbon dioxide utilization by microalgae have led towards sustainable and economically feasible biorefineries. Despite rapid advancements in algal bioprocess technologies, there is still a scope for improvement in the cell biomass productivities which will simultaneously improve the biofuels and biorenewables yields. In conclusion, this comprehensive review pinpoints the relevance of algal biomass valorization involving cost analysis which will lead towards a sustainable biorefinery paradigm with multifaceted applications. Graphical abstract: Unlabelled Image Highlights: Carbon capture by microalgae is both eco-friendly and cost-effective. The supplementation of CO2 enhances both biomass and bioproducts. Wastewater utilization for microalgae cultivation improves the economic feasibility. A CO2 -based biorefinery model is proposed for high-value biorenewables production.